2018
DOI: 10.1016/j.clml.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Italian Multicenter Study on Accuracy of 18 F-FDG PET/CT in Assessing Bone Marrow Involvement in Pediatric Hodgkin Lymphoma

Abstract: F-FDG PET/CT showed high diagnostic performance in the evaluation of BMI in pediatric HL. Thus, BMB should be ideally reserved for patients presenting with doubtful F-FDG PET/CT findings for BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…Our results showed a higher sensitivity of PET/CT 94.1% (95% CI, 81.6-100) in detection of BMI compared to BMB 35.3% (95% CI, 10-60.6). This is consistent with the study done by Cistaro et al [28], the sensitivity of 18F-FDG PET/CT was found 96% (95% CI, 89-100%) while that of BMB was found 38% (95% CI, 20-57%). This is also consistent with the study done by Büyükşimşek et al [29], who included 110 patients with HL and found PET/CT sensitivity was 91.3% (95% CI, 71.96-98.93) compared to that of BMB which was 56.52% (95% CI, 34.49-76.81).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed a higher sensitivity of PET/CT 94.1% (95% CI, 81.6-100) in detection of BMI compared to BMB 35.3% (95% CI, 10-60.6). This is consistent with the study done by Cistaro et al [28], the sensitivity of 18F-FDG PET/CT was found 96% (95% CI, 89-100%) while that of BMB was found 38% (95% CI, 20-57%). This is also consistent with the study done by Büyükşimşek et al [29], who included 110 patients with HL and found PET/CT sensitivity was 91.3% (95% CI, 71.96-98.93) compared to that of BMB which was 56.52% (95% CI, 34.49-76.81).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found a fair agreement between PET/ CT and BMB in HL cases by using Cohen's k, it was found 0.350 with p value less than 0.0001. This is consistent with the study done by Cistaro et al [28], who found also fair agreement between PET/CT and BMB findings as Cohen's k was found 0.398 with p value less than 0.001.…”
Section: Discussionsupporting
confidence: 92%
“…Bone marrow examination (marrow aspirate and trephine) is no longer routinely performed in the FDG-PET era. 3,4 Where PET imaging is unavailable for diagnostic staging, bone marrow examination may be considered for patients especially, for those with advanced-stage NLPHL identified on conventional cross-sectional imaging and/or adverse high-risk factors.…”
Section: Other Pre-treatment Investigationsmentioning
confidence: 99%
“…Indeed, a direct association has been shown between bone marrow glucose uptake and host systemic inflammation in cancer patients [ 259 ]. Furthermore, a diffusedly increased bone marrow FDG uptake can be present in patients due to increased hematopoiesis following administration of granulocyte-colony stimulating factors [ 260 ].…”
Section: Resultsmentioning
confidence: 99%